The gnostic new age : how a countercultural spirituality revolutionized religion from antiquity to today - De Conick, April D. (New York : Columbia University Press, 2016)
In The Gnostic New Age, April D. DeConick recovers this vibrant underground history to prove that Gnosticism was not suppressed or defeated by the Catholic Church long ago, nor was the movement a fabrication to justify the violent repression of alternative forms of Christianity. Gnosticism alleviated human suffering, soothing feelings of existential brokenness and alientation through the promise of renewal as God. DeConick begins in ancient Egypt and follows with the rise of Gnosticism in the Middle Ages, the advent of theosophy and other occult movements in the nineteenth and early twentieth centuries, and contemporary New Age spiritual philosophies.
The matrix of ancient spirituality -- The gnostic true man -- Supermen and monsters -- Paul and gnostic dogma -- John and the dark cosmos -- Gnostic altered states -- Hell walks and star treks -- Spiritual avatars -- The Pi of gnostic politics -- Pleasantville religions -- Gnosticism out on a limb.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
Added to collection customer.56279.3
Keywords: Gnosticism -- History; New Age movement; RELIGION -- Ancient; Gnosticism; New Age movement; Electronic books; History